ANALISIS PERMINTAAN UBI KAYU SEBAGAI INPUT PADA INDUSTRI KERUPUK SANJAI DI KOTA BUKITTINGGI - Mike Triani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aims to determine the effect of the price, number of workers, oil and other raw materials, Sanjai ouput to demand on an industrial cassava crackers Sanjai in Bukittinggi.The results showed that: variable price of cassava and no significant negative effect on the total output of cassava in Bukittinggi (Y), variable working tenagan positive and significant effect on the total output of cassava in Bukittinggi (Y), variable amount of the value of the raw material positive and significant impact on the demand for cassava in Bukittinggi (Y), variable production value positive effect and no significant effect on demand for cassava in Bukittinggi (Y), Keyword : demand, and production output